2012
DOI: 10.1159/000336760
|View full text |Cite
|
Sign up to set email alerts
|

The Triad of Pain, Fatigue and Depression in Ischemic Stroke Patients: The Bergen Stroke Study

Abstract: Background: Many patients with cerebral infarction suffer from symptoms such as pain, fatigue and depression. Most studies focus on single symptoms, but these symptoms often occur together. Whereas symptom clusters have been studied in cancer patients, little is known about different symptom clusters in patients with cerebral infarction. The aim was to evaluate clusters of co-occurring symptoms in the long term. We hypothesized that patients with cerebral infarction display distinct symptom clusters. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 46 publications
5
57
0
2
Order By: Relevance
“…21,24,27 One study reported that smoking cessation was associated with PSF in patients without depression, 14 suggesting that sudden abstinence of smoking may contribute to PSF. 51 Medications that are commonly used in patients with stroke such as sedatives, 27 antidepressants, 45,52 and hypnotics 17 may cause fatigue. Although studies have not implicated medications as a major cause of PSF, 14,34,47 the potential association should not be ignored.…”
Section: Medical Comorbidities Smoking and Medicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…21,24,27 One study reported that smoking cessation was associated with PSF in patients without depression, 14 suggesting that sudden abstinence of smoking may contribute to PSF. 51 Medications that are commonly used in patients with stroke such as sedatives, 27 antidepressants, 45,52 and hypnotics 17 may cause fatigue. Although studies have not implicated medications as a major cause of PSF, 14,34,47 the potential association should not be ignored.…”
Section: Medical Comorbidities Smoking and Medicationsmentioning
confidence: 99%
“…66 Although fatigue, pain, and depression are related conditions, poststroke pain seems to be more closely associated with fatigue than depression. 52,69 Pain may somehow be involved in the persistence of fatigue over time. 26 …”
Section: Painmentioning
confidence: 99%
“…Depression also has a negative effect on social functioning and the quality of life of patients [23,24,25,26]. …”
Section: Introductionmentioning
confidence: 99%
“…Further research to investigate the relationship between pain, fatigue and participation in community activities for individuals with SCI is warranted. Given previous attention paid to the pain-fatiguedepression symptom cluster in other populations, notably individuals with cancer 28 or post-stroke, 29 it is not surprising to see a relationship between these factors in this study. The directional nature of this cluster remains unclear and presents an opportunity for further interventional research to determine the nature of this phenomenon.…”
Section: Discussionmentioning
confidence: 62%